Performance of Paddy Cultivation under Different Methods in South-Western Part of Punjab, India - Gautam, Anand; Singh, Vicky; Aulakh, Gurjant Singh (Indian Journal of Extension Education, 2021)
To find out the most appropriate method of paddy sowing in Ferozepur district, a field experiment was conduct with different sowing methods at three locations including direct seeded, bed transplanting and mechanical rice transplantation. The maximum grain yield was found in conventional (80.67 q/ha) followed by, mechanical transplanted (78.35 q/ha),bed transplanted 24 plants per m2 (71.96 q/ha) sowing method as compared to DSR (77.40 q/ha). However, the ratio of benefit-cost was higher by direct seeded rice method (4.42:1) as compared to mechanical transplanted method (3.35:1), bed transplanted method (2.63:1)and conventional transplanted method (2.88:1). Higher Benefits cost ratio of direct seeded rice method was due to its lesser cost of field preparation, labour saving and water saving as compared to conventional method of sowing. The better net return obtained from direct seeded rice method Rs. 107881.94/ha as compared to mechanical transplanted method (Rs. 98975.00), conventional transplanted method (Rs. 94777.78/ha) and bed transplanted method (Rs. 80286.11/ha). Although the grain yields under conventional method of sowing was higher but it was unsuccessful to produce better net return and benefits of cost ratio.Direct seeded rice method provided timely sowing operation with better net return of paddyin Punjab.